Child Development Reviewed from Differences in Parental Personality Types - Heri Saputro; Linda Triani Rassita; Eva Agustina Yalestyarini; Intan Fazrin (Griya Eka Sejahtera, 2025)
Background: Childhood is a golden age, and if children don't receive quality stimulation during their toddler years, they will experience impaired emotional, social, mental, intellectual, and moral development. Parents play a crucial role in improving the quality of their children's development. This study aimed to determine the relationship between parental personality types and child development.Methods: This research design is a cross-sectional analytic study, with a population of all parents and children, with an average of 50 respondents per month. The sample size was 44 respondents using a simple random sampling technique. The collected data were processed using the Spearman Rho statistical test with a significance level of α = 0.05.Results: The results showed that of the 44 respondents, the majority (23 respondents (52.3%) had an introverted personality type, and nearly half (20 respondents (45.5%) had normal development.The Spearman Rho statistical test yielded a p-value of 0.002, which is less than 0.05, indicating a relationship between parental personality type and child development.Conclusion: The results of this study prove that a toddler's development is influenced by the parent's personality type, so it is hoped that parents have an extroverted personality so that the child develops well